The Effectiveness of an Islamic Education-Based Eco-Print Activity Learning Module in Enhancing Early Childhood Entrepreneurship Understanding at PAUD Kasih Bersama, Central Bengkulu - Ningmas Indri Oktaviana Octaviana; Alimni Alimni; Husnul Bahri (TANJAK, 2026)
This study aims to determine the effectiveness of an Islamic education-based eco-print activity learning module in enhancing early childhood entrepreneurship understanding at PAUD Kasih Bersama, Central Bengkulu. The study employed a mixed-methods approach using a sequential explanatory design, in which quantitative data were collected and analyzed first, followed by qualitative data to further explain the quantitative findings. The quantitative data were obtained through observation sheets administered as pretests and posttests to an experimental group of 12 children and a control group of 12 children. Qualitative data were collected through interviews, observations, and documentation. The findings indicate that the implementation of the Islamic education-based eco-print learning module improved children’s understanding of basic entrepreneurial concepts and related character traits, including creativity, independence, communication, responsibility, cooperation, honesty, and perseverance. The experimental group’s mean score increased from 36.08 in the pretest to 39.42 in the posttest. An independent samples t-test produced a significance value of 0.002, which was lower than 0.05, with a t-value of 3.558, exceeding the t-table value of 2.179. Qualitative findings further revealed increased enthusiasm, creativity, confidence, and active participation among the children. The integration of Islamic values, including gratitude, honesty, responsibility, patience, and environmental stewardship, also enriched the learning experience. Therefore, the Islamic education-based eco-print activity learning module is effective as a contextual and meaningful medium for introducing entrepreneurship to young children.